2019
DOI: 10.1002/jobm.201900383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen deficiency on the physiology and biochemical composition of microalga Scenedesmus rotundus‐MG910488

Abstract: The present investigation ascertains the impact of gradient concentrations of sodium nitrate on the physiology and biochemical composition of isolated microalga Scenedesmus rotundus-MG910488. The concentrations of nitrate were selected as 0, 3.5, 7.0, 10.5, 14.0, and 17.6 mM/L in BG 11 medium. The lower concentrations of nitrogen were found to be significantly decreasing the cell count and photosynthetic activity in the microalga as well as changing cell morphology.The amount of biomass, its productivity and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This observation also indicates that the absence of a nitrogen source alters the biosynthetic pathway to accumulate lipids. A study of Scenedesmus rofundus showed that high lipid content can be achieved under low nitrogen supply conditions (41.46 ± 1.94%) (Dixit 2019). Similarly, Ruangsomboon and Ganmanee (2013) reported that the highest lipid contents (20.3 ± 0.4% and 19.4 ± 0.4%) were obtained in nitrogen-and phosphorus-deficient media, respectively, for Scenedesmus dimorphus KMITL.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation also indicates that the absence of a nitrogen source alters the biosynthetic pathway to accumulate lipids. A study of Scenedesmus rofundus showed that high lipid content can be achieved under low nitrogen supply conditions (41.46 ± 1.94%) (Dixit 2019). Similarly, Ruangsomboon and Ganmanee (2013) reported that the highest lipid contents (20.3 ± 0.4% and 19.4 ± 0.4%) were obtained in nitrogen-and phosphorus-deficient media, respectively, for Scenedesmus dimorphus KMITL.…”
Section: Discussionmentioning
confidence: 95%
“…Phosphates are crucial for growth and development, the production of cellular components, fatty acid production, energy transport, respiration and photosynthesis (Yaakob et al 2020). A study of Scenedesmus rofundus showed that the highest lipid content (41.46±1.94%) was achieved under low nitrogen supply conditions (Dixit 2019). Scenedesmus bajacalifornicus BBKLP-07 achieved highest lipid content of 26.19% in cultivation under 25% CO2 (Patil and Katiwal 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, assimilation of various nutrients in the culture medium could lead to the production of various intracellular products, which could affect the content of biomass, pigments, and fatty acids [ 26 , 27 ]. Since different nitrogen concentrations have different accumulation conditions for various substances [ 28 , 29 ], the findings show that the changes in algal biomass were different from the changes in algal cell density.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, biotic and abiotic stresses were applied to green algae to enhance the lipid content of a limited available biomass (Rashid et al, 2020;Ananthi et al, 2021). For example, control of the nitrogen supply and type of sources (e.g., nitrate) increased the ratio of lipids to the weight unit (Dixit et al, 2020;Encinas-Arzate et al, 2020;Zhang et al, 2020). Nevertheless, increased lipid content was not accompanied by a positive effect on biomass productivity (Araujo et al, 2020;Toumi and Politaeva, 2021).…”
Section: Lipid Productivity and Contents From Biomass Producedmentioning
confidence: 99%